DIFFUSION OF SILICON AND GALLIUM (AS AN ANALOGUE FOR ALUMINUM) NETWORK-FORMING CATIONS AND THEIR RELATIONSHIP TO VISCOSITY IN ALBITE MELT - Baker D.R. (My University, 1995)
Self-diffusion of Si and tracer diffusion of Ga have been measured in an albitic melt, Na0.97Al0.99Si3.02O8, at 1 atmosphere between 1160 and 1558°C. Diffusion of these network-forming elements was studied for comparison with viscous transport and Nuclear Magnetic Resonance (NMR) relaxation parameters measured in albite melts and glasses. Gallium was used as an analogue for Al and estimated diffusion parameters for both Ga and Al are presumed to be equivalent. Diffusion can be described by Arrhenius lines for both Si and Ga (with 1-standard errors):+6.58 x 10-3DSi = 1.37 x 10-4 exp(-337.4 +/- 52.6/RT)-1.35 x 10-4+7.97DAl # DGa = 3.55 x 10-1 exp(-424.6 +/- 42.5/RT)-3.39 x 10-12 s-1 and activation energies are in kJ/mol. Comparison of Si and Ga diffusivities with Si diffusivities in crystalline albite indicates relatively small differences between activation energies for diffusion of 3+ and 4+ network-forming cations in crystalline and in molten albite. Apparently, the energy barrier to diffusion of these network-forming cations is influenced significantly only by nearest neighbours, and is not strongly affected by changing the dominant structure from four-membered rings of (Si, Al)O4 tetrahedra in crystalline albite to three-, four-, and six-membered rings of tetrahedra in molten albite. Comparison of Na diffusion in albite crystals and glass demonstrates significant differences in activation energies for diffusion. The behaviour of oxygen diffusion appears to be intermediate between Na and network-forming cations, however, this observation is based upon limited oxygen diffusion data for rhyolitic, not albitic, melts. Activation energies for Ga diffusion in albite melt are similar to those measured in rhyolite melt at 1.0 GPa. The silicon activation energy for diffusion is three times higher in albite melt than in rhyolite melt at 1.0 GPa and does not correlate with the activation energy for the inverse of the NMR spin-lattice relaxation. The differences between Si activation energies in albite and rhyolite melts are suggested to be due to the presence of a mixed alkali-like effect in the latter melt. Calculated diffusivities based upon measured viscosities for albite melt and the Eyring equation agree almost within error with Ga diffusivities, but are typically 3-10 times greater than Si diffusivities. This correlation suggests that diffusion of Al in albite melt controls viscous transport. The activation energy for oxygen diffusion in crystalline albite and the estimated activation energy for oxygen diffusion in the melt are much lower than the activation energy for viscous transport and argue against a relationship between oxygen diffusion and viscous transport in this aluminosilicate melt. The more rapid diffusion of Ga and Al compared to Si in albite melt is proposed to be due to the more frequent formation of five- or six-coordinated Ga-O and Al-O transition state complexes than similar Si-O complexes. The previously observed relationship between viscosity and chemical diffusivities during interdiffusion (Baker, 1992b) suggests that diffusion of Al also controls chemical diffusion in basaltic to rhyolitic melts.